FEATURES OF TEACHING THE RUSSIAN LANGUAGE IN UNIVERSITIES OF UZBEKISTAN - Norboeva Dilafruz (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article is devoted to the study of the role of the Russian language as a language of interethnic communication. In sovereign Uzbekistan, the quality of training of highly qualified specialists who speak Uzbek and Russian is of particular importance. In a strong mastery of the Russian language, the upbringing of interest and love for it plays an important role. In order for a student to become interested in a subject, he must understand why he is studying it, feel the beauty, richness, expressiveness of the Russian language, deeply understand why the Russian language has become the language of interethnic communication.